2011
DOI: 10.4194/1303-2712-v11_3_17
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The efficacy of clove oil as an anaesthetic was evaluated in Juvenile of Russian sturgeon (Acipenser gueldenstaedtii) under two experiments. Dose response examined using four anaesthetic concentrations varying from 0.22 to 0.90 g/L of clove oil and effect of exposure duration on the recovery time analysed for 5 and 10 min. Mean body length (cm), 24.9±1.37 and weight (g) 63.2±10.89, n=120, juvenile Russian sturgeon placed individually to the anaesthetic bath prepared with clove oil, and induction (I1: Sedation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 21 publications
0
4
1
Order By: Relevance
“…However, fish in treatment T 3 showed more homogeneity among them might be due to similar growth pattern. Collaborated with the FW and WG, significantly higher SGR was recorded in treatment T 1 followed by T 2 and T 3 which contradicts with the findings of Akbulut et al (2002) who reported that specific growth rate decreased with the increasing body size due to the faster growth rate of larger fish. SGR recorded in the present experiment was slightly lower than the findings of Kohinoor et al (2012) who also used the fish with similar initial weight (3.24 to 3.26 g) of our study.…”
Section: Growth Performance and Survivalcontrasting
confidence: 88%
“…However, fish in treatment T 3 showed more homogeneity among them might be due to similar growth pattern. Collaborated with the FW and WG, significantly higher SGR was recorded in treatment T 1 followed by T 2 and T 3 which contradicts with the findings of Akbulut et al (2002) who reported that specific growth rate decreased with the increasing body size due to the faster growth rate of larger fish. SGR recorded in the present experiment was slightly lower than the findings of Kohinoor et al (2012) who also used the fish with similar initial weight (3.24 to 3.26 g) of our study.…”
Section: Growth Performance and Survivalcontrasting
confidence: 88%
“…Due to its natural origin, low price, and ready availability, clove oil (or its main constituent, eugenol) is widely used as an anesthetic for fish species [1, 33, 34]. In Russian sturgeon juveniles, test concentrations of 450 to 900 mg/L were reported to meet the efficacy criteria specified for handling within 3 min, with recovery in 5 min and no mortality [35, 36]. Meanwhile, relatively higher doses of clove oil have been used to induce anesthesia of juveniles and subadults of white sturgeon ( Acipenser transmontanus ), with mean induction and recovery times for 1000 mg/L determined as 1.5 min and 16.3 min, respectively [37].…”
Section: Discussionmentioning
confidence: 99%
“…Imanpoor et al (2010) recommended a dose of 400 mg/L of clove oil to best anaesthetise Persian sturgeon (Acipenser persicus). Akbulut et al (2011b) considered an effective concentration to be 450-670 mg l -1 of clove oil for juvenile Russian sturgeon (Acipenser gueldenstaedtii). Feng et al (2011) stated that an effective dose is 120 mg/L of clove oil for juvenile Siberian sturgeon.…”
Section: Discussionmentioning
confidence: 99%
“…There are plenty of studies available on the anaesthetic dosage of clove oil (Hikasa, et al, 1986;Woody et al, 2002;Woolsey et al, 2004;Akbulut et al, 2011aAkbulut et al, , 2011bFeng et al, 2011) and benzocaine (Oswald, 1978;Mattson and Riple, 1989;Gomes et al, 2001) for pelagic fish species which are regarded as seeing-feeding fish, but comparative studies concerning the optimal dose and the effects of anaesthesia on feed intake for sturgeon species which forage on the bottom by touch with barbells (smelling-feeding fish species) are limited. Soto and Burhanuddin (1995) did, however, observe most rabbitfish (Siganus lineatus) feeding a few hours after anaesthesia with clove oil, Prince and Powell (2000) reported that adult rainbow trout (Oncorhynchus mykiss) fed actively 1 week after anaesthesia with clove oil, Pirhonen and Schreck (2003) stated that steelhead trout (Oncorhynchus mykiss) ate relatively well 4 h after anaesthesia with MS-222, clove oil and CO 2 and Sorum and Damsgard (2004) considered that benzocaine anaesthesia had only a minor and insignificant effect on feed intake in Atlantic salmon (Salmo salar).…”
Section: Bilalmentioning
confidence: 99%